Using positive deviance to enhance HIV care retention in South Africa: development of a compassion-focused program to improve the staff and patient experience - Allison J. Ober; Donald H. Skinner; Laura M. Bogart; Leletu Busakwe; Wadene Davids; Hassan Mahomed; Debbie Ling; Virginia Zweigenthal (BMC Global and Public Health)
Abstract Background HIV burden remains high in South Africa despite intensive efforts to curtail the epidemic. Public primary care facilities, where most people with HIV (PWH) in South Africa receive treatment, face myriad challenges retaining patients on antiretroviral therapy (ART). Nevertheless, some facilities manage to consistently retain PWH in care. We used a participatory positive deviance (PD) approach to discover characteristics of primary care facilities with above-average 12-month retention rates to develop an intervention. Methods We conducted 11 in-depth leadership interviews, 9 staff focus groups with 29 participants, 11 patient focus groups with 45 participants, 23 patient shadowing visits, and multiple facility observations in each of 3 high- and 3 low-retention public primary care facilities in Cape Town, South Africa. Using PD, an asset-based approach to behavior change that consists of discovering how high-performing outliers succeed despite sizable barriers, and then using those data to develop interventions for low performers, we analyzed data to discover dominant characteristics of higher-retention facilities that might be contributing to higher retention rates. Results Dominant themes found in higher-retention facilities were compassionate, respectful, and patient-centered care; higher staff morale, passion for the work, and team cohesion; efficient workflow procedures; and a welcoming physical environment. From these themes, we developed the multidimensional Connect intervention, consisting of strategies within three domains: (1) engage, encourage, and support staff (e.g., a monthly staff support huddle, a compassion training); (2) expedite and augment workflow procedures (e.g., adjust folder system to lower wait times); and (3) create a welcoming physical environment (e.g., fresh paint and plants in the waiting area). Conclusions A PD approach enabled us to identify factors that could be contributing to higher ART retention rates within low-resource public sector primary care facilities in Cape Town, South Africa, and to develop a multidimensional intervention. If effective after a future trial, the intervention could be a feasible, affordable complement to existing programs aimed at improving care for PWH.